Delivery of Nerve Growth Factor via Exosome Attenuates Neuropathic Pain in a Rat Model of Chronic Constriction Injury - Li, Yangyi; Chen, Chengbo; Su, Changsheng; Li, Shunyuan; Wen, Zhibin; Zheng, Yifan (Current Neuropharmacology, 2025)
<span class=
Keywords: Neuropathic pain